The neuroprotective effect of minocycline via tlr-4/nf-кβ signalling pathway in lipopolysaccharide - induced cognitive impairment in male rats - Qaid, Entesar Yaseen Abdo (2024)
Neuroinflammatory processes involving glial cell activation and the toll-like receptor 4/nuclear factor kappa B (TLR-4/NF-κB) signalling pathway have been implicated in cognitive impairment. Minocycline, has shown potential for regulating glial cell activation and reducing neuroinflammation. This study aimed to investigate the molecular mechanism of minocycline in lipopolysaccharide (LPS)-induced cognitive decline in the hippocampus of adult male Sprague-Dawley (SD) rats, comparing it to memantine. Fifty SD rats were randomly assigned to five groups: i) control treated with normal saline, ii) LPS (5 mg/kg) treated with normal saline, iii) LPS (5 mg/kg) treated with 25 mg/kg minocycline, iv) LPS (5 mg/kg) treated with 50 mg/kg minocycline, and v) LPS (5 mg/kg) treated with 10 mg/kg memantine. All treatments were administered once daily for two weeks via the intraperitoneal route. On day 5 of the experiment, intraperitoneal LPS injection was performed to induce a neuroinflammatory reaction and provoke learning and memory dysfunction. Morris Water Maze (MWM) and novel object recognition task (NORT) were used to assess learning, spatial memory, and recognition memory. Then, the rats were sacrificed, and hippocampal tissue was collected. Immunohistochemistry and Western blot were conducted to evaluate the expression of microglia and astrocyte markers, inflammatory, neurotrophic, and transcriptional proteins. The levels of oxidative molecules (malondialdehyde (MDA) and protein carbonyl (PCO)), antioxidant enzymes (catalase (CAT) and superoxide dismutase (SOD)), and phosphorylated tau proteins were measured using ELISA kits. Congo red and Cresyl violet staining were employed to assess amyloid accumulation and neuronal count. Minocycline treatment for two weeks conferred protection against LPS-induced gliosis, neuroinflammation, oxidative stress, amyloid accumulation, phosphorylated tau protein formation, neuronal loss, and learning and memory dysfunction. Notably, the neuroprotective effects of minocycline were comparable to memantine and exhibited dose-dependent with higher minocycline doses yielding greater neuroprotection. In conclusion, this study demonstrates that minocycline possesses potential preventive and therapeutic benefits against cognitive decline associated with neuroinflammatory diseases in humans. Its multifaceted mechanisms encompass anti-glial, anti-inflammatory, antioxidant, anti-amyloidogenic, and anti-tau protein properties, effectively ameliorating LPS-induced learning and memory impairments. These effects of minocycline were dose-dependent-the higher the dose, the better effects and comparable to memantine effects. These findings warrant further investigation of minocycline as an alternative therapy for cognitive decline in clinical settings.